Evaluating stroke early supported discharge using cost-consequence analysis. Issue 23 (6th November 2022) - Byrne, Adrian; Chouliara, Niki; Cameron, Trudi; Geue, Claudia; Lewis, Sarah; Robinson, Thompson; Langhorne, Peter; Walker, Marion F.; Fisher, Rebecca J.
Abstract: Purpose: To evaluate different stroke early supported discharge (ESD) services in different geographical settings using cost-consequence analysis (CCA), which presents information about costs and outcomes in the form of a balance sheet. ESD is a multidisciplinary service intervention that facilitates discharge from hospital and includes delivery of stroke specialist rehabilitation at home. Materials and methods: Data were collected from six purposively sampled services across the Midlands, East and North of England. All services, rural and urban, provided stroke rehabilitation to patients in their own homes. Cost data included direct and overhead costs of service provision and staff travel. Consequence data included service level adherence to an expert consensus regarding the specification of ESD service provision. Results: We observed that the most rural services had the highest service cost per patient. The main costs associated with running each ESD service were staff costs. In terms of the consequences, there was a positive association between service costs per patient and greater adherence to meeting the evidence-based ESD service specification agreed by an expert panel. Conclusions: This study found that rural services were associated with higher costs per patient, which in turn were associated with greater adherence to the expert consensus regarding ESD service specification. We suggest additional resources and costs are required in order for rural services to meet evidence-based criteria. Implications for rehabilitation: The main costs of an early supported discharge (ESD) service for stroke survivors were staff costs and these were positively associated with greater levels of rurality. Greater costs were associated with greater adherence to ESD core components, which has been previously found to enhance the effectiveness of ESD service provision. The cost-consequence analysis provides a descriptive summary for decision-makers about the costs of delivering ESD, suggesting additional resources and costs are required in order for rural services to meet evidence-based criteria.